Bank Sentral: Analisis Fungsi, Neraca, dan Instrumen Kebijakan Moneter dalam Struktur Perekonomian Nasional - Irwan M.A Baculu (Indo Publishing, 2026)
This article examines the strategic role of the central bank in maintaining monetary stability and the national financial system. The discussion focuses on three crucial aspects: the institutional functions of the central bank, the structure and dynamics of Bank Indonesia’s balance sheet, and the monetary policy instruments employed to achieve macroeconomic objectives. Utilizing a descriptive-qualitative approach based on a review of literature and regulations, the article highlights how Bank Indonesia fulfills its mandate to maintain the stability of the rupiah exchange rate, control inflation, and support sustainable economic growth. The findings indicate that the effectiveness of Bank Indonesia’s role relies heavily on the synergy between institutional design, policy transparency, and cross-sector coordination. With an adaptive organizational system and an accountable policy framework, Bank Indonesia serves as a key pillar in safeguarding national economic resilience amidst ever-changing global dynamics.